Decision Support System Group Of Learning Evaluation At SMA Negeri Lhokseumawe - Mulyadi; Azhar; Zulfan Khairil Simbolon; Hendrawati; Amirullah (Sean Institute, 2022)
Teachers as educators who have the main task of educating the nation's children to become the next generation who are intelligent and knowledgeable. Teachers can develop students' potential and motivate students to excel. The quality of teachers is influenced by the level of teacher performance in providing knowledge to students and the way of providing clear and appropriate material when teaching. Students must also be involved in the process of assessing the quality of the performance of teachers who have been teaching. Based on these problems, input from students about teacher performance is generally done manually by filling out a satisfaction questionnaire on the teaching and learning process. As a result, we require an assessment system and a model for the quality of learning, particularly in the core school subjects. The evaluation in teacher assessment uses the AHP (Analytical Hierarchy Process) method and group borda. The AHP model process is used to evaluate and improve the quality of student learning so that it can provide objective results. The stages of research using research and development include the first stage, namely the preliminary study stage, theoretical study, and planning stage. The variables measured included attendance, accuracy, ease of capturing material, and the ability to manage classes and formulate problems. The second stage is to test and revise the AHP and Borda models. The third stage is the feasibility test of the decision model with AHP and Borda. The result of the group model is to get the ranking value of each variable, and this value will be entered into the AHP model and the Borda group model. The Borda results are given by the school principal, vice principal, and policy makers. The results of the AHP Model value of K1 (Teaching Attendance Rate) with a priority weight value of 0.280, rank 2, K2 (Accuracy of Starting and Ending Study Hours) of 0.207, and ranking 4, K3 (Ease of Submission of Materials to Be Understood) of 0.295. 1, K4 (Ability to Manage Class Interaction) 0.217, ranking 3. The results of the board for selecting the best teacher: alternative A1 with a value of 0.24 ranking 3. Alternative A2 with a ranking value of 0.20; Alternative A3 with a value of 0.28 ranking 1. Alternative A4 with a value of 0.27 and a rating of 2. The results of this study are the assessment of students and each teacher from the AHP model. Furthermore, the results of the Borda group are in the form of rankings from policy makers. The results of the research are more objective because of the decision-making on the part of students and groups/policy-makers.